Towards improved handling of uncertainty in cost-benefit analysis: addressing the ‘price-quality’ and ‘communication’ dilemmas - Mouter, Niek; Holleman, Marc; Calvert, Simeon; Annema, Jan Anne (European Journal of Transport and Infrastructure Research, 2015)
An important limitation of Cost-Benefit Analysis (CBA) is the inherent uncertainty in estimations of future welfare effects. In this paper, we argue that consideration of the ‘pricequality’ dilemma and the ‘communication’ dilemma is useful to explain and improve the handling of uncertainty in CBA. The ‘price-quality’ dilemma refers to the trade-off between the quality of welfare effect estimations and the costs of providing these estimations. Instruments to produce good quality effect estimates (including uncertainties) can be expensive both in monetary terms and time. We discuss the application of probabilistic traffic models as a promising example of how the ‘price-quality’ dilemma can be solved. The ‘communication’ dilemma refers to the observation that both a poor communication and a too prominent communication of uncertainties can cause problems for decision-makers. We argue that cognitive psychological theory provides useful perspectives to solve this dilemma, by providing a psychological framework which might help to explain why different types of people process CBA information differently. The results of this research may enhance first insights into the questions how the two dilemmas can be solved.